Marketing Research of Priorities and Sources of Financing for Scientific, Technological and Sectoral Development of Russia - Irina Y. OKOLNISHNIKOVA; Viktor M. KATOCHKOV; Antonina I. UKHOVA; Elena V. TOPORKOVA (Communications of International Proceedings, 2021)
In the article, based on the study of the regulatory framework, special sources, as well as the experience of interaction between public authorities and local government and enterprises of the real sector of the economy, the key priorities and sources of funding for the scientific, technological and sectoral development of Russia are investigated and analyzed. The authors paid special attention to the study of the targets for the strategic development of scientific research and development. The article examines and analyzes the sources of financial support for the development of scientific research and development of the domestic economy high-tech industries.
Keywords: Marketing Research; Marketing Strategies; Sectoral Economics; Regional Economy; Marketing of Innovations.